2020
DOI: 10.3390/antiox9090821
|View full text |Cite
|
Sign up to set email alerts
|

Nephroprotective Effect of Cilastatin against Gentamicin-Induced Renal Injury In Vitro and In Vivo without Altering Its Bactericidal Efficiency

Abstract: Gentamicin is a used antibiotic that causes nephrotoxicity in 10–20% of treatment periods, which limits its use considerably. Our results have shown that cilastatin may be a promising therapeutic alternative in toxin-induced acute kidney injury (AKI). Here, we investigated its potential use as a nephroprotector against gentamicin-induced AKI in vitro and in vivo. Porcine renal cells and rats were treated with gentamicin and/or cilastatin. In vivo nephrotoxicity was analyzed by measuring biochemical markers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…It is speculated that this was caused by membrane rupture, releasing gentamicin into the cytoplasm. In turn, this triggers pro‐apoptotic proteins, which damage mitochondria, leading to the release of reactive oxygen species (ROS) and consequent inflammation (Jado et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is speculated that this was caused by membrane rupture, releasing gentamicin into the cytoplasm. In turn, this triggers pro‐apoptotic proteins, which damage mitochondria, leading to the release of reactive oxygen species (ROS) and consequent inflammation (Jado et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Once bound and internalized through endocytosis, gentamicin travels to the endoplasmic reticulum, Golgi apparatus, and lysosomes, causing a build-up of phospholipids, impacting on lipid metabolism, ultimately leading to apoptosis (Martínez-Salgado et al, 2007). (Jado et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, cilastatin prevents absorption of imipenem by increasing urinary excretion and reducing the concentration inside the tubular cells. Previous studies at our hospital and elsewhere showed that cilastatin is effective for reducing the nephrotoxicity of various drugs such as antibiotics [ 47 , 48 ], immunosuppressants [ 49 ], analgesics [ 50 ], and chemotherapeutics without modifying their therapeutic efficacy in target cells. Cilastatin has been shown to protect proximal tubular cells from apoptotic, oxidative, and inflammatory toxic damage induced by cisplatin both in vitro and in vivo by reducing or preventing cisplatin-induced AKI and its worsening [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Gentamicin enters the cells through megalin, a multiligand endocytic receptor located in the apical brush border, and damages the proximal convoluted renal tubule. 15,[118][119][120] Gentamicin forms ternary complexes with iron ions and following oxidation triggers the generation of ROS. 121 Gentamicin accumulates in lysosomes and produces lysosomal phospholipidosis, 122 leading to the impairment of the phosphatidylinositol cascade.…”
Section: Gentamicinmentioning
confidence: 99%
“…1). [13][14][15] In podocytes, the plasma membrane monoamine transporter (PMAT) and bisphosphonates mediate disruption of the podocyte cytoskeleton, causing cell death. 16,17 Modeling of kidney injury relies upon both in vivo and in vitro methods.…”
Section: Introductionmentioning
confidence: 99%